Neutrophil Migration in the Activation of the Innate Immune Response to Different Flavobacterium psychrophilum Vaccines in Zebrafish (Danio rerio) - Camila J. Solís; Matías Poblete-Morales; Sergio Cabral; Juan A. Valdés; Ariel E. Reyes; Ruben Avendaño-Herrera; Carmen G. Feijóo (Journal of Immunology Research)
Flavobacterium psychrophilum is a Gram-negative bacterium, responsible for the bacterial cold-water disease and the rainbow trout fry syndrome in freshwater salmonid fish. At present, there is only one commercial vaccine in Chile, made with two Chilean F. psychrophilum isolates and another licensed in Europe. The present study analyzed neutrophil migration, as a marker of innate immune activation, in zebrafish (Danio rerio) in response to different F. psychrophilum bath vaccines, which is the first step in evaluating vaccine effectiveness and efficiency in fish. Results indicated that bacterins of the LM-02-Fp isolate were more immunogenic than those from the LM-13-Fp isolate. However, no differences were observed between the same bacteria inactivated by either formaldehyde or heat. Importantly, the same vaccine formulation without an adjuvant only triggered a mild neutrophil migration compared to the complete vaccine. Observations also found that, after a year of storage at 4°C, the activation of the innate immune system by the different vaccines was considerably decreased. Finally, new vaccine formulations prepared with heat and formaldehyde inactivated LM-02-Fp were significantly more efficient than the available commercial vaccine in regard to stimulating the innate immune system.